2017
DOI: 10.5104/jiepeng.10.e17-004-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Multi-Electrode Effects on Electrovibration Tactile Stimulation

Abstract: Electrovibration is one of promising methods for tactile feedback in mobile devices because of its simplicity of the structure and principle. In order to increase the capability of tactile presentation with the electrovibration, we developed an electrovibration tactile display with 1 mm electrode resolution. Voltage to each electrode is controlled separately and the tactile display can present electrovibration stimulus distribution. We designed the tactile display and optimized the voltage waveform to avoid de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…The values were not largely changed under high-frequency conditions. The obtained trend was similar to the results of related studies [25,26]. One considerable reason for this trend is the attenuation of the applied voltage induced by the skin and devices [25].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The values were not largely changed under high-frequency conditions. The obtained trend was similar to the results of related studies [25,26]. One considerable reason for this trend is the attenuation of the applied voltage induced by the skin and devices [25].…”
Section: Resultssupporting
confidence: 90%
“…The width and length of electrodes for each stimulus were 0.9 mm and 18 mm, respectively. The electrode designs were determined on the basis of the results of related studies, considering the spatial stimulation [26,27]. A pad for electrical connection was formed at the end of the electrode.…”
Section: Principle and Designmentioning
confidence: 99%
“…The threshold voltage was almost constant at 80 Hz or higher. Previous studies have revealed that the tactile perception to electrovibration is almost constant at high frequency [ 24 , 25 , 30 ]. We also confirm the same trend, although the size of the electrode was narrower than that of the previous studies.…”
Section: Resultsmentioning
confidence: 99%
“…The applied voltage to each electrode was a pulse wave. The duty ratio of the applied voltage was 10% to avoid breakdown of the insulator layer [ 30 ]. It was possible to vary the peak voltage from 0 V to 600 V with the scroll bar of the evaluation system.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation